A Review of Uplift Capacity of Enlarged Base and Anchor-Type Foundations in Geogrid Reinforced Sand Bed - V, Lakshmi; Raju, K. V. S. B.; S., Chinmay (AMC Indian Journal of Civil Engineering, 2024)
Anchor-type and enlarged-base foundations are among the most commonly used foundation types for structures subjected to tensile or uplift forces. Uplift forces act on piles, especially in expansive soils, where swelling can occur. Therefore, understanding the behavior of piles under uplift forces and the factors influencing their uplift capacity is crucial. These anchors are typically designed based on the weight of the overlying soil, which depends on the burial depth, as well as the frictional resistance from failure surfaces during load failure. One method to enhance the uplift capacity of foundations, without increasing burial depth, is by incorporating geogrid materials. This paper aims to provide a comprehensive review of the uplift resistance of enlarged-base and anchor-type foundation elements in cohesionless soils, both with and without geogrid reinforcement. The concepts of optimal size, placement, and number of geogrid layers are explored. Additionally, the paper discusses the influence of various factors, such as reinforcement, embedment ratio, and soil type.